The Storytelling Method for the Development of Language Skills in the Industrial Age 4.0 Towards the Golden Generation in 2045 - Sumarti Sumarti (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Please write the abstract in English maximum length 150 words. These instructions give you guidelines This study aims to describe how to train language skills (listening, speaking, writing and reading) using the online mode of storytelling in distance learning. This learning pattern is expected to provide better language skills in the industrial era 4.0. This study uses a qualitative descriptive method starting with the selection of materials, arranging interactive events, preparing tools and materials. The online storytelling method has some potential to be used to improve language skills. The results of this study indicate: 1) the storytelling method in online mode can be done interactively, 2) the four language skills can be trained by the storytelling method, 3) storytelling material can be integrated with other subjects; 4) the understanding of the story can be expressed through pictures and narration. What needs to be strengthened is the school's communication with parents related to enriching activities that improve language skills in children.Keywords: storytelling; language skills; industrial era 4.0